Photocatalytic water splitting for large-scale solar-to-chemical energy conversion and storage - Hisatomi, Takashi; Wang, Qian; Zhang, Fuxiang; Ardo, Shane; Reisner, Erwin; Nishiyama, Hiroshi; Kudo, Akihiko; Yamada, Taro; Domen, Kazunari (Frontiers in Science, 2024)
Sunlight-driven water splitting allows renewable hydrogen to be produced from abundant and environmentally benign water. Large-scale societal implementation of this green fuel production technology within energy generation systems is essential for the establishment of sustainable future societies. Among various technologies, photocatalytic water splitting using particulate semiconductors has attracted increasing attention as a method to produce large amounts of green hydrogen at low cost. The key to making this technology practical is the development of photocatalysts capable of splitting water with high solar to hydrogen energy conversion efficiency. Also necessary are advances that enable the deployment of watersplitting photocatalysts over large areas and the ability to recover hydrogen safely and efficiently from the oxyhydrogen gas produced. This article describes the key discoveries and recent research trends in photosynthesis using particulate semiconductors and photocatalyst sheets for overall water splitting, via one-step excitation and two-step excitation, or "Zscheme" reactions, as well as for direct conversion of carbon dioxide into renewable fuels using water as an electron donor. We describe the latest advances in solar water-splitting systems and pathways to improve their future performance, together with challenges and solutions in their practical application and scalability, including fixation of particulate photocatalysts, hydrogen recovery, safety design of reactor systems, and approaches to separately generate hydrogen and oxygen from water.